The quality of parenting in reproductive donation families: A meta-analysis and systematic review. Issue 6 (December 2022) - Zanchettin, Liviana; Tallandini, Maria Anna; Gronchi, Giorgio; Zito, Gabriella; Ricci, Giuseppe; Russo, Lucia Roberta
Abstract: This review examined whether the absence of a genetic link with one or both parents in families using reproductive donation induced a different quality of parenting from that found in families with spontaneous conception or autologous assisted reproductive technology (AUT-ART), where the genetic mother carries the pregnancy and both parents have a genetic link with their children. MEDLINE, PsycINFO and PubMed were searched for English-language studies published from January 1993 to October 2021. A total of 45 studies were included in the systematic review, and 11 in the meta-analysis. The meta-analysis showed that in reproductive donation families, where there was no genetic link between parents and children, there were higher positive parental values ( P  = 0.007) and lower negative parental values ( P  = 0.007) than for parents and children in families that had spontaneously conceived. No statistically significant differences emerged when the reproductive donation families were compared with the AUT-ART families. The study showed that the quality of parenting was not conditioned by the presence or absence of a genetic link; instead, it was influenced by the processes underlying family building, such as the desire to have a child, the involvement of both parents in the childcare and the quality of disclosure.